Civil society action against transnational corporations: implications for health promotion. (22nd August 2019) - Anaf, Julia; Baum, Fran; Fisher, Matthew; Friel, Sharon
Abstract: Transnational corporations (TNCs) shape population health both positively and negatively through their national and international social, political and economic power and influence; and are a vital commercial determinant of health. Individual and group advocacy and activism in response to corporate products, practices or policy influences can mediate negative health impacts. This paper discusses the unequal power relations existing between TNCs that promote their own financial interests, and activists and advocates who support population and environmental health by challenging corporate power. It draws on interview data from 19 respondents who informed 2 health impact assessments conducted on TNCs; 1 from the fast food industry, and 1 from the extractive industries sector. It reveals the types of strategies that civil society organizations (CSOs) have used to encourage TNCs to act in more health promoting ways. It discusses the extent to which these strategies have been effective, and how TNCs have used their power to respond to civil society action. The paper highlights the rewards, and the very real challenges faced by CSOs trying to change TNC practices related to health, within a neoliberal policy environment. It aims to provide evidence for socially oriented actors to inform their advocacy for changes in public policy or corporate practices that can contribute to improving population health and equity and tackling commercial determinants of health.